2004
DOI: 10.1002/marc.200400118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Atmosphere on the Reactivity of Peroxidic Species upon Photooxidation of Polymers

Abstract: Summary: This paper gives an account of preliminary results about the impact of an oxidative atmosphere on peroxidation. Attention is focused on the level, nature, and reactivity of (hydro)peroxides with respect to the oxidative component concentration. Our main result is surprising: a lower peroxidation rate occurs, but a higher content of hydroperoxides are formed in air than in pure oxygen atmospheres. The results may lead to an approach to understand the influence of atmospheric factors on the outdoor weat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…We believe that the balance in the formation/homolysis of hydroperoxides seems to be controlled by the oxidative atmosphere composition. 21 Gijsman and Sampers reported similar results for polyethylene. 22 The relationship between the formation of carbonyl groups or the decline in mechanical properties and the oxygen uptake was found to be dependent on the type of weathering, especially on the temperature and the oxygen pressure.…”
Section: Impact Of Oxidative Environmental Atmospheresupporting
confidence: 73%
See 1 more Smart Citation
“…We believe that the balance in the formation/homolysis of hydroperoxides seems to be controlled by the oxidative atmosphere composition. 21 Gijsman and Sampers reported similar results for polyethylene. 22 The relationship between the formation of carbonyl groups or the decline in mechanical properties and the oxygen uptake was found to be dependent on the type of weathering, especially on the temperature and the oxygen pressure.…”
Section: Impact Of Oxidative Environmental Atmospheresupporting
confidence: 73%
“…21 Thus, we assume that photodegradation chemistry strongly depends on environmental conditions such as oxygen pressure. We believe that the balance in the formation/homolysis of hydroperoxides seems to be controlled by the oxidative atmosphere composition.…”
Section: Impact Of Oxidative Environmental Atmospherementioning
confidence: 99%
“…619 Asphaltene contents increased during aging whereas resin, aromatics, and saturate contents decreased. 619 Asphaltene contents increased during aging whereas resin, aromatics, and saturate contents decreased.…”
Section: Pavementsmentioning
confidence: 94%
“…Also, in polyurethane studies, the degradation rate was estimated by determining amine and hydroxyl equivalent. 528 Differential scanning calorimetry was used to determine peroxide concentration in polymeric medium. 161,218,527 A specimen of degraded material is cryogenically ground to a fine powder and a swelling solvent is used to loosen crosslinked particles (if needed) or the material is dissolved in a suitable solvent.…”
Section: Titrimetrymentioning
confidence: 99%
“…Of these methods, hydroperoxide titration is the most suitable since hydroperoxides are common by-products of photooxidation. 528 Long experience with hydroperoxide titration has shown that several influences have to be considered to make results useful for further interpretation. Hydroperoxides are determined by iodometric titration.…”
Section: Titrimetrymentioning
confidence: 99%